A liquid biopsy model to detect eventual pollutants as "one health" tool. (20th October 2021) - Pepe, F; Scotti, G; Barbieri, O; Vozzella, EA; Iervolino, A; Malapelle, U; Troncone, G
Abstract: Environmental pollution (EP), defined as the unfavorable chemical and physical alterations of our surroundings, still represents a relevant issue of this century. In this scenario, several changes may directly or indirectly impact on human health by promoting neoplastic cell transformation due to DNA damage in human tissue. The identification of a specific molecular signature observed in people exposed to environmental contaminants could improve risk calculation of exposition. As regards, DNA methylation is considered an epigenetic modification that could play a pivotal role in the risk calculation of patients under EC exposure. This mechanism, based on the introduction of methyl groups on cytosine's in CpG islands, is carried out by methyltransferases enzymes able to activate this modification in promotor region by influencing regulation process. Several studies demonstrated that methylation pattern is drastically alterated in subjects under EC exposure. To date, several approaches for the early detection of contaminants in biological fluids are under investigation. Liquid biopsy consists in a peripheral blood withdrawn where several biomolecules [cell-free DNA (ccfDNA), circulating tumor cells (CTCs), circulating cell-free RNA (ccfRNA) and exosomes] may be isolated. Students participate to the validation of a LP assay for the evaluation of environmental determinants with the Lab Residents. They assessed the cost-efficacy and the minimally invasive approach in order to construct a reliable model to be exported for the identification of epigenetic changes in the early stage of contamination process in high risk people. The young students role was also to create an informative schedule in order to explain the role and the potential of Liquid biopsy as a non-invasive tool that could allow the analysis of nucleic biomarkers as circulating cell-free DNA (ccfDNA), a potential stable biomarkers of diverse disease conditions in humans and animals.